Antibacterial and Antifungal studies on Schiff Base Complexes by the Minimum Inhibitory Concentration (MIC) method (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The aim of the present study is to study the antibacterial and antifungal activities of the binuclear Schiff Base complexes of Ni (II) and Cu(II) metal salts. The plan of the research work was to analysed the molar inhibitory concentration (MIC) in molar concentration (*10*) of FAHMC (Furan-2-aldehyde 8-amino-7-hydroxy-4-methyl coumarin) and its Metal Ni(II) and Cu (II) complexes. The results were found that molar inhibitory concentration the Furan-2-aldehyde 8-amino-7-hydroxy-4-methyl coumarin FAHMC= Furan-2-aldehyde-8-amino-7-hydroxy-4- methyl coumarin. [Cu (FAHMC)₂] =Furan-2-aldehyde-8-amino-7-hydroxy-4- methyl coumarin. Cu(II) and [Ni (FAHMC)₂ (H2O)₂] =  Aqua furan-2-aldehyde-8-amino-7-hydroxy-4-methyl Ni(II). The results support hypothesis.